Heterofullerene-linked metal–organic framework with lithium decoration for storing hydrogen and methane gases. (8th March 2019) - Xu, Genjian; Meng, Zhaoshun; Liu, Yuzhen; Guo, Xiaojian; Deng, Kaiming; Lu, Ruifeng
Abstract: Hydrogen and methane are considered as the promising fuels in the future, however, one of the obstacles to their utilizations is the lack of efficient storage and safe transportation materials. In this theoretical work, a novel kind of metal–organic framework (MOF) is designed using heterofullerene as linker from density functional theory calculations and first-principles molecular dynamics simulations. Based on grand canonical Monte Carlo simulations, we explore the adsorption performances of H2 and CH4 in the proposed porous MOF materials, which exhibit spectacular capacities for hydrogen storage as well as for methane storage after Li doping, both achieving the targets set by U.S. Department of Energy at workable conditions. Graphical abstract: Image 1 Highlights: A new type of MOF utilizing C48 B12 as a part of linkers is designed for gas adsorption. New force field parameters are fitted to consider interactions between gas molecules and novel MOF structures. GCMC simulations exhibit high H2 and CH4 storage capacities in Li-decorated C48 B12 -MOF materials.